Mobilising Krishna’s World: The Writings of Prince Savant Singh of Kishangarh, by Heidi R. M. Pauwels - Lutjeharms, Rembert (Religions of South Asia, 2023)
Mobilising Krishna’s World: The Writings of Prince Savant Singh of Kishangarh, by Heidi R. M. Pauwels. Seattle: University of Washington Press, 2017. xvi + 262 pp. $30 (pb). ISBN 9780295742236.